IMBT ANTARA DSN DENGAN BANK SYARI’AH - Aulil Amri (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
This study is to analyze al ijarah muntahiah bi tamlik financing according to the national syari'ah council and its application in Islamic banking, and analyzing its conformity according to the prevailing regulations that is the fatwa of National Syari’ah Council Number 27 / DSN-MUI / III / 2002 about al-Ijarah al-Muntahiyah bi al-Tamlik. The results show that some of the Islamic banking transaction is already in accordance with the Islamic Shari'a but there are still al ijarah muntahiah bi tamlik practices that are not appropriate or deviate from the fatwa of the National Syari’ah Council. The deviation is like multi-faith practice for example the tenant becomes the owner of the object automatically with the final rental repayment without any new transaction. The function of the National Syari’ah Council as the supervisor of transaction activities at the syari'ah financial institution is not running properly, this causes the illegal transactions of Islamic banks to grow rapidly developed. Keyword: Dewan Syariah Nasional, Ijarah Muntahiah bi Tamlik, Islamic Banking.